VD_FINDINFO HC / 2014 / 144 vom 24. Januar 2014 - VD Tribunal cantonal (2014)
MAJORITÉ{ÂGE}, OBLIGATION D'ENTRETIEN, MESURE PROVISIONNELLE, RELATIONS PERSONNELLES | 277 al. 2 CC, 286 al. 2 CC, 261 al. 1 CPC (CH), 303 al. 1 CPC (CH)